(2x-5)-(x-3)=

Simple and best practice solution for (2x-5)-(x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-5)-(x-3)= equation:


Simplifying
(2x + -5) + -1(x + -3) = 0

Reorder the terms:
(-5 + 2x) + -1(x + -3) = 0

Remove parenthesis around (-5 + 2x)
-5 + 2x + -1(x + -3) = 0

Reorder the terms:
-5 + 2x + -1(-3 + x) = 0
-5 + 2x + (-3 * -1 + x * -1) = 0
-5 + 2x + (3 + -1x) = 0

Reorder the terms:
-5 + 3 + 2x + -1x = 0

Combine like terms: -5 + 3 = -2
-2 + 2x + -1x = 0

Combine like terms: 2x + -1x = 1x
-2 + 1x = 0

Solving
-2 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 0 + 2
1x = 0 + 2

Combine like terms: 0 + 2 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 2x+3x-6=0 | | KFC=kma | | logx+log(x+1)=12 | | d-67=33 | | 3x+x+96=180 | | 2p-qr= | | u=6(9n+31)+7(n+1) | | 40-5d=18d | | 314+2=350 | | 0.50x=55+(x-70)0.33 | | x+11x+24=0 | | 5-2(x+5)=39 | | 20x+30=14x+6 | | 50.45m+60=57.95m | | t^4+43t+42=0 | | 466/20= | | 4.37(4s)+3.43s=62.73 | | 5x+3(5x-18)=108 | | 9(6x-8)=26 | | p^3-1p=0 | | 6(4x-8)=20 | | 1x*5=49 | | 12=m-(-6) | | 8-6=-8 | | 1.1z+-3.3=-8.8 | | 4y-18=6 | | 7(x-8)=35 | | A=2(x)(x)(x)+3(x)(x)+6 | | x^2+21x+10=0 | | 0.15(c+9)=0.9 | | x^5-2x^3-4x=0 | | -0.85(n+3)=3.4 |

Equations solver categories